Pelatihan Keterampilan Dasar Konseling untuk Tenaga Pendidik dan Kependidikan - Euis Nurhidayati; Fatchiah E. Kertamuda; Tita Rosita; Raden Mutiara Puspa Wijaya (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Counseling is a professional assistance process in solving problems. However, in order to provide counseling, it is necessary to develop basic counseling skills. The objective of basic counseling skills training at PKBM 31 Jakarta is to improve the professional competence of educators in solving student problems so that they can create an inclusive, responsive learning environment that supports the holistic growth of students. The method used in community service is Service Learning (SL). The training activities in this service consist of three stages, namely (a) identification of learning problems at PKBM 31 Jakarta; (b) provision of basic counseling skills material; (c) counseling practice; (d) post-training evaluation. Based on the results of the community service, the following data was obtained from the problem identification: (1) there is a lack of knowledge among educators in overcoming psychological and social problems and the diverse learning needs of students at PKBM 31 Jakarta, while there are no educators with a background in guidance and counseling to help solve these problems; (2) Knowledge and understanding related to basic counseling skills for educators increased, enabling them to identify student problems and understand the appropriate responses and strategies for resolving student issues. Thus, basic counseling skills training for educators at PKBM 31 Jakarta was effective in improving educators' knowledge and understanding in resolving student problems.